Primary Osseous Tumors of the Spine - Bernard, Stephanie A.; Brian, Pamela L.; Flemming, Donald J. (Seminars in Musculoskeletal Radiology, 2013)
Primary osseous spinal tumors are relatively rare in comparison with metastatic disease, myeloma, and lymphoma. Despite their rarity, the interpreting radiologist must be aware of the typical imaging features to provide appropriate diagnosis for guidance of clinical management. The age of occurrence, distribution longitudinally in the spine, and distribution axially within the vertebra combined with typical imaging appearances can help indicate the correct diagnosis. This article reviews the diagnostic features of benign and malignant primary bone spinal tumors.
Keywords: primary spine tumors; bone tumor; benign tumor